From: archive Goldman, no. 21. Photographed at New York. With a dedication on back: 'To my friend Emma Goldman, Justus H. Schwab, March 18, 1901' - Spiess, Hm.
From: archive Goldman, no. 21. Photographed at New York. With a dedication on back: 'To my friend Emma Goldman, Justus H. Schwab, March 18, 1901'.